Management of organic waste into liquid fertilizer and compost welcoming the blue economy of Rancabungur - Nur Aini; Djamarel Hermanto; Pudji Winarko (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Global waste management is estimated that every year, only 20% can be recycled or recovered. The rest is a problem because of the generation of waste that pollutes various ecosystems and has an impact on decreasing the value of environmental services. The blue economy concept of Rancabungur Village is a new discourse of development in Rancabungur that accelerates economic growth, community welfare, and environmental health. One of the efforts to increase economic growth is to increase public awareness of managing waste which can later produce economic value, creativity, and the environment. The purpose of this activity is to provide an understanding to the target audience about the importance of waste management, to socialize the importance of sorting waste, and to provide training on processing organic waste into organic liquid fertilizer and compost so that it can increase family income. This activity is carried out live and online. After getting material on waste management and management. The results show that participants who want to manage waste want their surrounding environment to be healthy and beautiful as much as 88.2%, followed by managing waste can make money as much as 48.5%, waste management 29.1%, trust management rate 20.6% and need a more detailed explanation 19.1%. This activity will provide solutions to problems that develop in the community, increasing people's income.